Wonderful Things: The Discovery of Tutankhamun's Tomb - Harry Burton (USA The Metropolitan Museum of Art, 1976)
Text abridged and adapted from the Tomb of Tut Ankh Amen, by Howard Carter and A.C. Mace, 3 vols., 1923-1933.
Keywords: General; Ancient Egypt; Archaeology